A jugoszláv városhálózat rang-nagyság eloszlásának változásai - Reményi, Péter (Közép-Európai Közlemények, 2010)
During the existence of Yugoslavia its settlement system underwent serious alterations. The turbulent political geographical changes often transformed this system from the several creation of the state to the several dissolutions. After the birth of Yugoslavia its settlement system showed a polycentric pattern due to the various historical regions it included. Until the first breakup this polycentricity decreased a lot, but bipolarity (Belgrade-Zagreb) remained as a consequence of interwar politics of Yugoslavia. After the 2nd WW the system steadily headed towards a harmonic, ideal pattern –according to the terms of Auerbach thesis or Zipf rule– which lasted until 1991. From this turning point the fundamentally changed political geographical environment caused the settlement structure to be changed as well. Seeing as a whole, the settlement system of the former Yugoslavia started to be more polycentric again (Belgrade declining, the new capitals growing). Looking at the individual successor states we can state that monocenticity is general except in Kosovo, but there are differences in sub categories of monocentricity. Croatia, Serbia and Macedonia have classical primatecities, while Bosnia-Herzegovina inherited a bipolar system again due to the political situation. Montenegro and Slovenia are in between, with a monocentric system with strong second cities.